NUMERICAL SIMULATION AND RELIABILITY SENSITIVITY ANALYSIS OF BIONIC KILLER WHALES’S LOAD CHARACTERISTIC - LI MingHao; QIAO Jie; ZHAO LiJuan; WANG BaoXin; FAN JiaYi; GAO CunQiang (Jixie qiangdu)
As a kind of bionic robot fish,bionic killer whale played an important role in ocean development and scientific investigation. Based on the flapping wing movement theory,the bionic killer whale’s mechanism was analyzed,its instantaneous load was simulated by MATLAB. Based on the stress-strength interference theory,the bionic killer’s load reliability state function was established,the reliability index and reliability of bionic killer whale was calculated,combined with the reliability sensitivity analysis theory,the dimensionless sensitivity was obtained,analyzed the influence of the bionic killer whale’s design variables to reliability sensitivity gradient. This paper provides the theoretical basis,accurate data support and an effective numerical calculation method for the design and optimization of the bionic underwater robot with flapping wing theory as the propeller,which has important practical engineering significance.